PAI TEACHERS' EFFORTS TO INCLUDE HONESTY AND DISCIPLINE IN LEARNING IN GRADE 4 STUDENTS AT SDN 3 UNGGA - Fathul Husna Sholehah (Sinar Lima, 2025)
This research is concern about honesty and discipline, which must be instilled from an early age, starting in elementary school. This research is motivated by the need for improvement in the level of honesty and discipline at SDN 3 Ungga. Instilling honesty and discipline requires effort to instill them in everyone. Therefore, this study focuses on the efforts of Islamic Religious Education teachers in instilling honesty and discipline, as well as the supporting and inhibiting factors. This research is a descriptive qualitative study. Data collection techniques used observation, interviews, and documentation. Data analysis techniques employed data condensation, data presentation, and drawing conclusions. Data validity checked through extended observations, increased persistence, and triangulation. The research results show that (1) Islamic Religious Education teachers' efforts to instill honesty in fourth-grade students at SDN 3 Ungga were achieved through providing understanding related to honesty, role models, and advice. Meanwhile, instilling discipline was achieved through role models, advice, and rewards. (2) Supporting factors for these Islamic Religious Education teachers' efforts were the school environment, cooperation between teachers, and cooperation between teachers and parents. Meanwhile, inhibiting factors were students' fear of admitting mistakes and social interaction.